PEMANFAATAN KEANEKARAGAMAN SUMBERDAYA TUMBUHAN OLEH MASYARAKAT BADUY-DALAM DI SEKITAR GUNUNG KENDENG SELATAN, KABUPATEN LEBAK, BANTEN BAGIAN SELATAN - Wardah Wardah (BERITA BIOLOGI, 2003)
Kendeng mountain, where "Baduy-Dalam" community lives is a native reserve area.Observation around "leuweung kolot","leuweung ngora", and "leuweung lembur" near the community area shows how the Baduy-Dalam community controls the sustainability of their forests.These forests are almost untouchable.Information on the biodiversity of plant species in the areas have not known yet.A study on the knowledge of Baduy-Dalam community and utilization of plant resources in Cikeusik,Cikertawana, and Cibeo villages was conducted.The results shows that the Baduy-Dalam tribe had a close relationship with their surroundings; it is seen from their knowledge in managing the environment in order to survive and continuing their living.Among 163 plant species recorded, 81 species are as potential food plants (the largest group), 38 species of medicinal plants, 17 species of building materials, 8 species for ritual, 17 species for fire wood, 4 species handycraf, 3 species economically potential, and 1 species for drinking. There are two species is considered as endangered species namely Arcangelisia Jlava and Alstonia scholaris.